136 DIABETES IS ASSOCIATED WITH IMPAIRED PERIPHERAL AND CEREBRAL HAEMODYNAMIC RESPONSES IN OLDER ADULTS. (25th October 2022) - Hernandez, B; Dyer, A; Nipoti, B; McCrory, C; Briggs, R; Kennelly, S; Finucane, C; Romero-Ortuno, R; Reilly, R; Kenny, RA
Abstract: Background: Diabetes is associated with slower gait speed and adverse brain health outcomes in older adults. However, the putative mechanisms underlying these associations remain poorly explored. One such mechanism is via altered cerebral perfusion, which may represent an important intermediate phenotype in the association between diabetes and slower gait. We assessed the impact of diabetes on peripheral and cerebral haemodynamic responses during active stand as part of The Irish Longitudinal Study of Ageing (TILDA). Methods: We assessed: (i) peripheral haemodynamic responses (heart rate, blood pressure, cardiac output) using finometry and (ii) Tissue Saturation Index (TSI) using Near-Infrared Spectroscopy (NIRS) during active stand in older adults. Function-on-scalar regressions were used to model the impact of diabetes on the dynamic response to standing. Subsequently, multivariable linear models were used to model usual gait speed. Results: Of 3, 011 older adults (mean age: 64.2; 55.2% female) completing active stand, diabetes (n =193, 6.4%) was associated with significantly higher heart rate (mean 3.2, s.e. 0.02 bpm), higher cardiac output (mean 0.16, s.e. 0.04 L/min) and lower systolic blood pressure (mean –6.9, s.e. 1.8 mmHg) during standing. Additionally, diabetes was associated with significantly lower TSI from 10 seconds post-stand (mean –1.2%, s.e. 0.49%). Associations persisted following robust covariate adjustment. Diabetes was associated with significantly slower gait speed (-5.3 cm/s, CI (-8.4, -2.1)). In analysing the relationship between cerebral perfusion and gait speed, poorer recovery of TSI at 60-120 seconds post standing was associated with slower gait speed (0.53 cm/s slower gait speed per unit increase in TSI, p = 0.007). Conclusion: Diabetes is associated with impaired peripheral and cerebral haemodynamic responses in addition to slower gait speed in community-dwelling older adults. Neuro-cardiovascular instability and altered cerebral perfusion may represent an important intermediate phenotype between diabetes and adverse health outcomes in older adults.